Study on the linkage mechanism between key strata fracture in overburden and surface subsidence during caving mining in extra-thick coal seams - Tianwei Lan; Zhijia Zhang; Weiqiang Guo; Zhu Li; Guoqiang Wu; Ping Fang (Scientific Reports)
Abstract Caving mining in extra-thick coal seams induces large-scale overburden movement, leading to more intense fracture processes in key strata, more significant surface subsidence, and frequent dynamic disasters in mines. This study, using the N34-2 caving face of the 17th coal seam at Junde Mine as a case study, aims to investigate the time-varying linkage mechanism between surface subsidence, microseismic characteristics, and fracture scales of the overburden’s key strata under such mining conditions. Based on Timoshenko’s theory, a bearing fracture mode for the overburden’s key strata is proposed, and corresponding fracture criteria are established. The fracture modes and step distances of the N34-2 working face were calculated theoretically and verified using microseismic localization data, showing that higher key strata are more prone to bearing failure, leading to a significant increase in fracture step distances. Numerical simulations and surface monitoring techniques were employed to comprehensively analyze the main controlling factors for surface subsidence. To further clarify the linkage mechanism between the fracture of high-position key strata and surface subsidence, the full fracture cycle under extra-thick coal seam caving mining is divided into four sub-processes: short-term fracture, rapid movement, compaction stability, and energy accumulation. The dynamic relationship between overburden movement, microseismic data, and surface subsidence responses is analyzed for each sub-process, establishing a time-varying linkage system. This approach offers a more systematic and accurate method to predict and assess the overburden movement and fracture processes, providing new insights for the prevention and control of rock burst disasters in extra-thick coal seams.